Psoriasis Treatment Changes the Expression Profile of Selected Caspases and their Regulatory MicroRNAs - Wcisło-Dziadecka, Dominika; Simka, Klaudia; Kaźmierczak, Agata; Kruszniewska-Rajs, Celina; Gola, Joanna; Grabarek, Beniamin; Hybiak, Jolanta; Grillon, Catherine; Mazurek, Urszula; Łos, Marek J. (Cellular physiology and biochemistry, 2018)
Background/Aims: Psoriasis, an autoimmune diseases of the skin, characterized by patches of abnormal/inflammed skin, although not usually life-threatening, it causes severe discomfort, esthetic impairments, and may lead to impaired social functions and social withdrawal. Besides UV-phototherapy, various anti-inflammatory treatments are applied, depending on the severity of symptoms. In 2008, adalimumab (fully humanized human anti-TNF antibody) was launched for the treatment of psoriasis. In the quest to better understand the pathomechanism of adalimumab’s therapeutic effects, and the acquired resistance to the drug, we have investigated how its administration affect the regulation of the expression of selected caspases, including those activated by inflammosome. Methods: The research was initially carried out on normal human dermal fibroblasts (NHDF) treated with adalimumab for 2, 8 and 24 hours in vitro. Then, expression profile of genes encoding caspases and their regulatory micro-RNAs was determined with the use of oligonucleotide microarray. The validation of the microarray results was carried out by qRT-PCR. The in vitro study was followed by ex-vivo investigation of adalimumab’s effects on the expression of caspase-6 in blood of the psoriatic patients. The samples were collected before, and 2 hours after adalimumab’s administration and the analysis was determined by qRT-PCR. Results: The result of the analysis indicated that introduction of adalimumab to the NHDF culture resulted in the change of the transcription activity of genes encoding caspases and genes encoding miRNAs. The analysis revealed 5 different miRNA molecules regulating the expression of: CASP2, CASP3 and CASP6. There were no statistically significant differences in the expression of gene encoding caspase-6 in the patients’ blood before and 2 hours after the anti-TNF drug administration. Conclusion: We have found that adalimumab administration affects caspases expression, thus they may be used as molecular markers for monitoring the therapy with the use of an anti-TNF drugs, including adalimumab. It is likely that the mechanisms responsible for changed expression profiles of genes encoding caspase-2,-3, and -6, may be caused by the upregulation of the respective microRNA molecules. Increased expression of genes encoding specific caspases may induce inflammatory processes, as well as trigger apoptosis. Furthermore, the proapoptotic activity of caspases may be enhanced by miRNA molecules, which exhibit proapoptotic function. The overexpression of such miRNAs was observed in our study.